Digital Photography and Photographic Editing - Ricky Telg (EDIS)
WC094, a 4-page illustrated fact sheet by Ricky Telg, is first in a three-part series that offers tips on taking good digital photos and addresses the basics of digital photography. Includes additional sources of information. Published by the UF Department of Agricultural Education and Communication, July 2010.